Digital Literacy of Economics Teachers in Senior High Schools in Minahasa Regency (A Qualitative Case Study) - Helmi Rorimpandey; Allen Manongko; Meike Drita Mamentu (ITScience (Information Technology and Science), 2026)
This study aims to analyze the digital literacy of economics teachers in several public high schools in Minahasa Regency. The main informants in this study were 11 economics teachers, plus supporting informants consisting of 3 students and 3 school principals. The data analysis technique used was the interactive analysis model by Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. This study used a qualitative approach, collecting data through interviews. First, most economics teachers have a positive perception of digital technology, viewing it as an effective tool for improving material delivery, facilitating access to information, and making learning more engaging for students. This is evident in the use of digital media, including interactive presentations, instructional videos, and online learning platforms. Second, teachers' digital pedagogical practices have largely been implemented, albeit at a basic level, such as delivering material, assigning work, and evaluating through digital platforms. The use of digital technology still needs improvement to make learning more innovative, interactive, and student-centered. Third, teachers face obstacles such as limited technical skills, technological facilities, and a lack of training that supports digital literacy. Overall, the digital literacy of economics teachers at the research site has begun to develop, but still requires improvement through training programs, facility support, and school policies that support the use of digital technology in learning.